Efficient synthesis of quinoxalines in the ionic liquid 1-n-butylimidazolium tetrafluoroborate ([Hbim]BF4) at ambient temperature - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Quinoxaline derivatives have been synthesized in excellent yields using an ionic liquid (IL) (viz., 1-n-butylimidazolium tetrafluoroborate) as a reaction medium as well as promoter from various 1,2-diketones and aryl-1,2-diamines. The process is general for the synthesis of quinoxaline derivatives from aromatic as well as aliphatic-1,2-diketones. The advantages of the present method are ambient reaction temperature, simplicity of operation, high yields of products, the recyclability of the IL, and ecofriendly nature of the reaction medium.
Keywords: 1; 2-diamines; 2-Diketones; Aryl-1; ionicliquid(IL); quinoxalines